SYNTHESIS AND CHARACTERIZATION OF CA2AL2SIO7:PR3+ PHOTOLUMINESCENCE MATERIALS BY BALL-MILLING METHOD - Bimarjuna, Bimo
Pathogens are defined as organisms that can cause diseases in their hosts. Therefore, to eliminate pathogens such as SARS-COV-2, the roles of various parties are needed to prevent its spread. One of the practical efforts to reduce transmission in public places is to develop antipathogenic coatings on frequently touched surfaces in public facilities. A UVC light- emitting lamp (200-280 nm) was recently reported to be very effective in killing SARS-COV- 2 virus in two minutes at a distance of one meter. The photoluminescence material Ca2Al2SiO7 doped with Pr3+ has been reported to emit UVC light in the wavelength range of 265-270 nm. Photoluminescence material Ca2Al2SiO7 doped with Pr3+ can emit UVC light for more than 10 hours when excited at a wavelength of 254 nm. In addition, Ca2Al2SiO7 is environmentally friendly, easy to modify, and has good thermodynamic stability. In this study, the ball-milling method was used to synthesize Ca2Al2SiO7:Pr3+, in addition to the conventional solid-phase method. This study aimed to determine the effect of variations in the synthesis on the photoluminescence properties of Ca2Al2SiO7:Pr3+. Variations in the ratio of ball mass to sample mass (1:20, 1:30, and 1:40) and milling speed (150 rpm and 400 rpm) were successfully synthesized using the ball-milling solid phase method, based on X-ray diffraction characterization and analysis with the Rietveld method. The optical properties of Ca2Al2SiO7:Pr3+ were analyzed using photoluminescence (PL) spectroscopy. The successful synthesis of Ca2Al2SiO7:Pr3+was confirmed from the diffraction pattern at 2? ? 28°, 32°, dan 37°. The PL spectrum of Ca2Al2SiO7:Pr3+ showed that the sample emitted UVC at wavelengths of 275 and 315 nm. Increasing the sample mass ratio and milling speed also decreases the intensity of the PL spectrum. The maximum emission intensity was obtained with conventional solid-phase synthesis. The decrease in intensity is thought to be due to impurities during the milling process, as seen in the SEM-EDS analysis, where metal impurities were present outside the main constituent of the sample, namely Cr-Fe-Ni. Experimental facts can be used to understand the effect of variations in synthesis using the ball-milling method. This synthesis variation can affect the structural changes, changes in energy levels, and types of electronic transitions in the compound Ca2Al2SiO7:Pr3+. This experimental fact is used effectively to increase the photoluminescence intensity of solids so that they can be applied as self-sanitized pathogen exterminators.